2021
DOI: 10.1016/j.stem.2020.11.005
|View full text |Cite|
|
Sign up to set email alerts
|

Capture of Mouse and Human Stem Cells with Features of Formative Pluripotency

Abstract: Summary Pluripotent cells emerge as a naive founder population in the blastocyst, acquire capacity for germline and soma formation, and then undergo lineage priming. Mouse embryonic stem cells (ESCs) and epiblast-derived stem cells (EpiSCs) represent the initial naive and final primed phases of pluripotency, respectively. Here, we investigate the intermediate formative stage. Using minimal exposure to specification cues, we derive stem cells from formative mouse epiblast. Unlike ESCs or EpiSCs, form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
246
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(254 citation statements)
references
References 127 publications
5
246
3
Order By: Relevance
“…FA-RAS KO ESC showed high expression of OTX2, which has been shown a critical transcription factor for thew maintenance of intermediate states of pluripotency (7). The consequence of having high levels of OTX2 in this context can be inferred by previous studies (25).…”
Section: Fa-rasmentioning
confidence: 76%
See 3 more Smart Citations
“…FA-RAS KO ESC showed high expression of OTX2, which has been shown a critical transcription factor for thew maintenance of intermediate states of pluripotency (7). The consequence of having high levels of OTX2 in this context can be inferred by previous studies (25).…”
Section: Fa-rasmentioning
confidence: 76%
“…Finally, we showed that FA-RAS KO ESC can be maintained in culture under primed conditions and could be a suitable genetic model to study intermediate states of pluripotency. Indeed, FA-RAS KO ESC mirrored transcriptionally cells that have departed 12-24 hours from naïve pluripotency and are reminiscent of the recently described pluripotent intermediate states (6)(7)(8). Future studies will be necessary to determine the similarity of all these intermediate states with corresponding in vivo counterparts.…”
Section: Fa-rasmentioning
confidence: 92%
See 2 more Smart Citations
“…In 2020, three other groups have reported the pioneering of 2D culture conditions which support stable in vitro derivation and maintenance of intermediate pluripotent embryonic states. 3,8,9 All these states show cell polarity, a transcriptome indicative of formative pluripotency and, as far as assayed, 8 glycolytic metabolism. Surprisingly, comparative analysis of the transcriptomic and epigenomic data generated by these groups 3,8,9 and in the current study 6 show that the intermediate pluripotent ESCs in each of the culture conditions resemble different time points in the naïve-to-primed transition, over a timespan ranging from approximately E5.0 to E6.5 6 (Fig.…”
mentioning
confidence: 99%